Mild Isolated Hyperthyrotropinemia Variants Database - Tellechea, Mariana Lorena (2025)
This Systematic Review was conducted in the context of the following project: "Variation Spectra in Mild Isolated Hyperthyrotropinemia: Pilot Cohort and Systematic Review". The purpose was to provide further evidence for the elucidation of the genetic etiology of Mild Hyperthyrotropinemia and to expand the phenotypic and variant spectrum of Congenital Hypothyroidism. We performed a systematic review and reclassification of the disease-causing potential of gene variants using the recommendations of the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP).